APPLICATION OF QUEST TECHNOLOGIES IN THE TRAINING OF HIGHER EDUCATION ATTENDERS (FROM THE EXPERIENCE OF LESYA UKRAINKA VOLYN NATIONAL UNIVERSITY) - TROFIMUK-KYRYLOVA, Tetyana; KARPIUK, Alina; CHYBYRAK, Svitlana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Annotation. The article examines the peculiarities of quest technologies and justifies the expediency of their use in educational institutions. Thanks to a constructive approach, quests are used in the organization of the educational process in higher education. Quest technologies combine the ideas of the project method, problem-based and game-based learning, team interaction and the use of information and communication technologies. Their use makes it possible to apply new ways of developing educational content. The article analyzes the experience of Lesya Ukrainka Volyn National University regarding the use of quests in the training of students of the specialties 027 «Museum studies, monument studies» and 029 «Information, library and archival case» was analyzed. The possibilities of using traditional quest-excursions and webquests in order to create conditions for practice- and resource-oriented training, which is aimed at a holistic approach to the organization of the educational process, are considered. The subjects of the cognitive activity are the participants of the quest, for whom the ability to find a way (ways) to solve problem situations is important. It has been established that quest technologies represent tasks with game elements. The practice of organizing quests at the Lesya Ukrainka Volyn National University confirms that during their implementation, various tasks are often combined. This allows students to develop originative and creative abilities, analytical thinking, the ability to work in a team and other competencies. It is emphasized that the use of quest technologies in the training of higher education students contributes to the formation of their motivation for educational and cognitive activities. The article describes the advantages of integrating individual online services into the educational process. The practical implementation of webquests using the LearningApps online service and the Kahoot digital service is shown. It has been confirmed that the use of quest opportunities in higher education institutions creates favorable conditions for self-education and development of students and scientific and pedagogical workers. The development and solving of various tasks during traditional or web quests forms in the participants of the educational process the skills of cognitive activity, analyzing situations and solving problematic questions, the ability to work in a team. The experience of conducting quests for students of the specialties 027 «Museum studies, monument studies» and 029 «Information, library and archival case» showed that quest technologies have a didactic potential.